2019
DOI: 10.1177/1833358319826351
|View full text |Cite
|
Sign up to set email alerts
|

Health records as the basis of clinical coding: Is the quality adequate? A qualitative study of medical coders’ perceptions

Abstract: Background: Health records are the basis of clinical coding. In Portugal, relevant diagnoses and procedures are abstracted and categorised using an internationally accepted classification system and the resulting codes, together with the administrative data, are then grouped into diagnosis-related groups (DRGs). Hospital reimbursement is partially calculated from the DRGs. Moreover, the administrative database generated with these data is widely used in research and epidemiology, among other purposes. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 42 publications
1
56
0
4
Order By: Relevance
“…Medical records affect the coded data for a range of reasons, including unclear documentation and variations in the description of diagnoses. Therefore, the use of these standards can be effective in diagnostic coding and audits to improve the quality of coded data (28). The present study also confirmed the impact of non-compliance with diagnostic principles (31.6%) and medical records legibility (17.2%) on the given codes.…”
Section: Discussionsupporting
confidence: 78%
“…Medical records affect the coded data for a range of reasons, including unclear documentation and variations in the description of diagnoses. Therefore, the use of these standards can be effective in diagnostic coding and audits to improve the quality of coded data (28). The present study also confirmed the impact of non-compliance with diagnostic principles (31.6%) and medical records legibility (17.2%) on the given codes.…”
Section: Discussionsupporting
confidence: 78%
“…First, harmonisation of clinical EORTC/MSG definitions with existing Australian Coding Standards may help safeguard accurate detection of IFI in the coded data by reducing ascertainment of false positive cases (for example, our high number of false positive cases [N = 38] coded as 'candidiasis of other sites' [code B37.88]). In fact, recent qualitative research proposes the use of Systematized Nomenclature of Medicine-Clinical Terms (SNOMED-CT) codes in electronic health records as a more granular tool to standardise terminology and facilitate clinical coding of complex diseases [25,31,32]. Second, ensuring that chart documentation is complete, legible and streamlined will ensure clinical coders have sufficient access to the data required to assign the appropriate IFI code(s) [25,33,34].…”
Section: Plos Onementioning
confidence: 99%
“…Methods to assess the quality differed across studies. One approach to assessing quality involved focus groups and interviews of Health Information Managers and coders [1,2]. This qualitative research found problems in completeness, accuracy, and consistency in coding.…”
Section: Quality Of Ehr Datamentioning
confidence: 99%